Psycho Social Compatibility And Its Relation With Self Esteem Of Students At Sciences And Techniques Of Physical And Sports Activities Institution. - Barkati , Nasereddin (sports creativity, 2025)
The study aimed at identifying the relationship between the psychological compatibility and self esteem of students at physical education class. The researcher used the descriptive method which fit the nature of the study on a population of about 96 second year Master students at physical education class at Science and Techniques of physical and Sport Activities. And about 40 students were chosen as a sample on which the study tool is applied. It is represented in the psychological compatibility and self esteem measures of Koper Smith. The study showed that: there is a positive association between the high psychosocial compatibility and self esteem of students at physical education class. It showed also that there is a positive association between average psychosocial compatibility and self esteem of students at physical education class. As it shows that there is a positive association between the low psychosocial compatibility and self esteem of students at physical education class